Magical Means of Dealing with Ghosts in Ancient Mesopotamia - Scurlock, Jo Ann
Ph.D. Dissertation; December 1987; Supervisor: W. Farber. Dissertation committee: E. Reiner, R. D. Biggs, M. Gibson; includes editions or re-editions of magical texts concerned with expelling ghosts, as well as necromancy texts and incantations in which appeal is made to ghosts for assistance.